2018
DOI: 10.1111/jfb.13650
|View full text |Cite
|
Sign up to set email alerts
|

Counterintuitive migration patterns by Atlantic salmon Salmo salar smolts in a large lake

Abstract: What little is known about the seaward migration of Salmo salar smolt migration through standing waters indicates that it is both slow and results in high mortality rates, compared with riverine migration. This may be partly because smolts in lakes need to swim more actively and require more complex directional cues than they do in rivers. In this telemetry study of smolt migration through Loch Lomond, S. salar smolts made repeated movements in directions away from the outflowing river, which considerably incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(43 citation statements)
references
References 10 publications
7
36
0
Order By: Relevance
“…Tagged smolts showed migratory behavioral patterns that were both similar and distinct to other migratory salmonid populations experiencing high predation risks. Residence period and rate of movement of smolts while migrating indicated that a shorter time spent within the river was related to migration success, corroborating the notion that the River Endrick is a high-risk landscape for salmonid juveniles (Furey et al 2016, Honkanen et al 2018, Furey et al 2021). Despite the evidence of high predation pressure found in the river, smolts travelled during the day, especially as they moved further downstream.…”
Section: Discussionsupporting
confidence: 67%
“…Tagged smolts showed migratory behavioral patterns that were both similar and distinct to other migratory salmonid populations experiencing high predation risks. Residence period and rate of movement of smolts while migrating indicated that a shorter time spent within the river was related to migration success, corroborating the notion that the River Endrick is a high-risk landscape for salmonid juveniles (Furey et al 2016, Honkanen et al 2018, Furey et al 2021). Despite the evidence of high predation pressure found in the river, smolts travelled during the day, especially as they moved further downstream.…”
Section: Discussionsupporting
confidence: 67%
“…Similarly, lacustrine–adfluvial S. trutta can migrate through other lakes to reach their destination lake (Huusko et al ., ). Given that both mortality and energy expenditure of salmonid smolts are considerably increased in passage through lakes compared with rivers (Honkanen et al ., ; Schwinn et al ., ), it might be expected that S. trutta smolts would not continue through a lake unless programmed to do so. In coastal Californian rivers, summer sandbars at estuary mouths result in seasonally closing estuaries that form small productive freshwater lagoons.…”
Section: Migration Destinationmentioning
confidence: 98%
“…A number of diadromous fish species have experienced dramatic declines throughout their range due to disruption of habitat connectivity due to anthropogenic barriers such as weirs, dams and hydropower facilities (Dadswell and Rulifson 1994;Birnie-Gauvin et al 2018;Puijenbroek et al 2019). Many freshwater systems have anthropogenic barriers impeding fish movement, as well as lakes that diadromous fishes must navigate through to reach the marine environment (Limburg and Waldman 2009;Nunn and Cowx 2012;Honkanen et al 2018Honkanen et al , 2021. How diadromous fishes navigate through standing waters is poorly understood (Honkanen et al 2018;Lennox et al 2021;Honkanen et al 2021).…”
Section: Introductionmentioning
confidence: 99%